AL-KUTUB AL-MADRASIYAH AL-‘ARABIYAH FĪ INDŪNISIYĀ MIN MAẒŪRI WAṬANĪYIN WA ‘ĀLAMĪYIN - Pransiska, Toni; Sugiyono, Sugeng; Widodo, Sembodo Ardi; Sayyid, Wael Aly Muhammad (Universitas Islam Negeri Ar-Raniry, 2024)
The study of school textbooks is interesting to examine comprehensively and in-depth. The issues with textbooks can be mapped into three crucial problems: First, issues related to the preparation and assessment phase. Second, issues related to the distribution of books, including accessibility and the purchasing power of textbooks. Third, problems related to the usage of books. This research focuses on developing a comprehensive assessment instrument for Arabic language textbooks. The researcher conducted research and development using the ADDIE model, which was developed from the instruments of the National Education Standards Agency (BSNP), the American Council on the Teaching of Foreign Languages (ACTFL), and the Common European Framework of Reference for Languages (CEFR), as well as expert opinions. The results of this research and development show: First, the development of a comprehensive assessment instrument for Arabic language textbooks, consisting of four components: appearance, content, language, and presentation or teaching. Each component has indicators and sub-assessment items, totaling 50 assessment items. Second, the instrument was tested on Arabic language textbooks published by the Ministry of Religious Affairs, with a resulting score of 77.48, indicating they are suitable with major revisions needed.